1997
DOI: 10.1076/phbi.35.4.227.13306
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Investigation and in vitro Antimalarial Activity of Tabebuia ochracea ssp. neochrysantha

Abstract: A study of Tabebuia ochracea ssp. neochrysantha, a plant traditionally used in the Amazon against malaria, was pursued. Bioactivity was tested in vitro against Plasmodium berghei and Plasmodium falciparum (FcB2 chloroquine-resistant strain). Inhibitory activity was determined by measuring parasite 3 H-hypoxanthine incorporation. Fractionation of the chloroformic extract of P. ochracea (inner stem bark) afforded five furanonaphthoquinones. The highest antimalarial activity against P. berghei was given by a mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…In the Bignoniaceae family, naphthoquinones is the principal group of secondary metabolites. There are reports dealing with the following activities for these compounds: antimalarial (Pérez et al, 1997), antitumor (Ueda et al, 1994), anticancer (Abbott et al, 1967), antifungal (Guiraud et al, 1988), antibacterial and anti-inflammatory (Zani et al, 1991 …”
Section: Resultsmentioning
confidence: 99%
“…In the Bignoniaceae family, naphthoquinones is the principal group of secondary metabolites. There are reports dealing with the following activities for these compounds: antimalarial (Pérez et al, 1997), antitumor (Ueda et al, 1994), anticancer (Abbott et al, 1967), antifungal (Guiraud et al, 1988), antibacterial and anti-inflammatory (Zani et al, 1991 …”
Section: Resultsmentioning
confidence: 99%
“…neochrysantha (Pérez et al, 1997) and T. avellanedae (Fujimoto et al, 1991) bark and have been shown to possess important activity against rodent and human malaria parasites Plasmodium berghei and P. falciparum (Pérez et al, 1997), respectively. Also, compound 1, extracted from dry T. avellanedae bark, is active in vitro against several types of malignant tumor cells and was patented in Japan in 1994 (Derwent, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It consists of exposing larvae to test sample in saline solution, and lethality is evaluated after 24h. Lethality assay has been used successfully to bioguide the isolation of cytotoxic (Siqueira, et al, 1998), antimalarial (Perez, et al, 1997), and insecticidal (Oberlies, et al, 1998) compounds from plant extracts. Also, this test has been used as a model to evaluate compounds for their ability to protect against superoxide-mediated toxicity (Matthews, 1995).For toxicity evaluation of plant extracts by brine shrimp bioassay, an LD 50 value lower than 1 mg/mL is considered active (Meyer, et al, 1982).Therefore, to verify the toxicity of crude extracts from aerial parts of E. Suberosum, the ability to induce Artemia salina death was evaluated.…”
Section: Brine Shrimp Lethality Testmentioning
confidence: 99%
“…It consists of exposing larvae to test sample in saline solution, and lethality is evaluated after 24h. Lethality assay has been used successfully to assess compounds presenting cytotoxic (Siqueira, et al, 1998), antimalarial (Perez, et al, 1997), and insecticidal (Oberlies, et al, 1998) activities from plant extracts. In the toxicity evaluation of plant extracts by brine shrimp bioassay, an LD 50 value lower than 1 mg/mL is considered active (Meyer, et al, 1982).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation